2014
DOI: 10.1016/j.ihj.2014.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Use of ‘Guideliner’ catheter to overcome failure of delivery of Absorb™ Bioresorbable Vascular Scaffold in calcified tortuous coronary lesions: Technical considerations in ‘Real World Patients’

Abstract: In our series of 177 real world patients (223 lesions) who underwent Absorb Bioresorbable Vascular Scaffold (BVS) implantation, 78 lesions were calcified and tortuous lesions. In four of these, despite adequate lesion bed preparation, appropriate guiding catheter support and use of buddy wires, the BVS failed to track through the proximal calcified and tortuous coronary anatomy (CTCA). "Guide Liner" catheter (GLC) had to be finally used to resuccessfully deliver and implant BVS to the lesion site. We report fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Factors associated with successful outcomes were found to have appropriate preparation for complex lesion interventions, prediction of the need for devices (eg, Guideliner) used for crossing complex lesions and operator experience for these devices. [15][16][17] We found that in-hospital complication rates (2.7%) were similar with rates observed in previous studies with metal stents. 18 were severely calcified and rupture occurred as the operator followed aggressive post-dilation approach in order to achieve optimal scaffold follow-up period suggesting more common rates in real-life.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Factors associated with successful outcomes were found to have appropriate preparation for complex lesion interventions, prediction of the need for devices (eg, Guideliner) used for crossing complex lesions and operator experience for these devices. [15][16][17] We found that in-hospital complication rates (2.7%) were similar with rates observed in previous studies with metal stents. 18 were severely calcified and rupture occurred as the operator followed aggressive post-dilation approach in order to achieve optimal scaffold follow-up period suggesting more common rates in real-life.…”
Section: Discussionsupporting
confidence: 87%
“…MACE rates (0.9%) in the present study were consistent with previous studies. ABSORD 2 and ABSORB EXTEND reported stent thrombosis related with ABSORB BVS as 1%, nonetheless, GHOST‐EU trial which evaluated real‐life data revealed thrombosis rate of 2.1% in 6‐months follow‐up period suggesting more common rates in real‐life . Lower adverse event rates in the present study when compared with real‐life data of ABSORB BVS might be related with performance of all procedures in a single‐center by a single operator, prescription of new P2Y12 inhibitors (off‐label) in combination with ASA, and finally post‐dilation in all lesions.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…While there have been earlier studies evaluating the use of BRS in calcified lesions. [15][16][17], this is the first large clinical prospective registry study involving BRS scaffolds that look at the impact of lesion calcification on long term clinical outcomes at 2 years.…”
Section: Discussionmentioning
confidence: 99%